The Improvement of Blade Element Momentum Theory in Horizontal Axis Wind Turbine Performance Analysis - Wan Muhammad, Wan Nur Azrina (Progress in Aerospace and Aviation Technology, 2023)
The present work uses the blade element momentum theory method for evaluating the performance of horizontal axis wind turbine. The wind turbine performances are described in term of the thrust coefficient CT, torque coefficient CQ and the power coefficient CP. The blade element momentum theory (BEMT) represents the wind turbine performance prediction method as result of combining two methods, namely the blade element theory (BET) and the momentum theory (MT). Both theories are able to formulate the axial forces and torques which work on the blade. Equating axial force and torque formulated by BET is equal axial force and torque by MT, makes one allows the axial induction factor and the angular induction factor a^’, the unknown quantities, can be defined and furthermore the wind turbine performances can be evaluated. The BEMT method used here is the combination of BEMT. The implementation this method as the tool for predicting the wind turbine performances are work well. However, for wind turbine configuration need a little adjustment, especially in setting the hub radius rh where the blade element momentum theory starts to make calculation from the inner blade to the tip. The high pitch angle and a relatively a large chord length at rh, make the BEMT fail to converge. In addition to the present work found that the three wind turbine performance coefficients are formulated by using the momentum theory is less accurate compared with BET formulation.